2013
DOI: 10.1536/ihj.54.11
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Prosthesis-Patient Mismatch May Be Negligible in Elderly Patients Undergoing Conventional Aortic Valve Replacement for Aortic Stenosis

Abstract: SummaryTogether with aging of the Japanese population, aortic valve replacement (AVR) for aortic stenosis (AS) is now becoming more and more common in the elderly. When the aortic annulus is too small to allow an adequate sized prosthetic valve, aortic root enlargement is required to avoid prosthesis-patient mismatch (PPM). However, age-related comorbidities including aortic root calcifi cation bring signifi cant risk in performing aortic root enlargement. In the present study, 40 patients aged 75 years or mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
5
0
2
Order By: Relevance
“…4) In our hospital, small annulus requiring root enlargement has traditionally been a contraindication of MIAVR. 2) Kitamura, et al reported that moderate prosthesis-patient mismatch did not have negative impact on survival or reduction of left ventricular mass index in elderly patients; 5) however, aortic valve replacement using a small mechanical valve would deteriorate quality of life in elderly patients. Based on our experience of performing more than 200 cases of MIAVR, we decided to perform aortic valve replacement with a bioprosthesis following root enlargement through a right mini-thoracotomy for the patient.…”
Section: Discussionmentioning
confidence: 99%
“…4) In our hospital, small annulus requiring root enlargement has traditionally been a contraindication of MIAVR. 2) Kitamura, et al reported that moderate prosthesis-patient mismatch did not have negative impact on survival or reduction of left ventricular mass index in elderly patients; 5) however, aortic valve replacement using a small mechanical valve would deteriorate quality of life in elderly patients. Based on our experience of performing more than 200 cases of MIAVR, we decided to perform aortic valve replacement with a bioprosthesis following root enlargement through a right mini-thoracotomy for the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Аналогичная связь прослеживается между РРМ и развитием послеоперационной сердечной недостаточности, отдаленной летальностью и замедлением регрессии гипер-трофии ЛЖ [3,18]. При развитии РРМ происходит уменьшение сердечного выброса в послеоперационном периоде, оно наиболее выражено в группе тяжелого несоответствия [8,19]. В нашей работе у больных обеих групп исходно была сохранная насосная функция сердца, она незначительно изменялась в раннем послеоперационном периоде в обеих группах (см.…”
Section: Discussionunclassified
“…The average age of our study group was relatively young with only two patients over the age of 65. Several studies have demonstrated that the presence of severe or moderate PPM did not influence long‐term outcome, left ventricular mass regression, and quality of life in elderly patients undergoing AVR . Degenerative aortic valve in the elderly often results in aortic stenosis with more calcified cusps and annulus.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that the presence of severe or moderate PPM did not influence long-term outcome, left ventricular mass regression, and quality of life in elderly patients undergoing AVR. 29,30 Degenerative aortic valve in the elderly often results in aortic stenosis with more calcified cusps and annulus. A continuous suture in a severely calcified ring easily leads to suture tearing and increases the incidence of paravalvular leakage.…”
Section: Discussionmentioning
confidence: 99%